Фемтосекундная лазерная обработка ри из "волкар" для создания на нём наноструктурного слоя - Костюк, Геннадий Игоревич (НТУ "ХПИ", 2017)
Для случая действия фемтосекундного лазера на твёрдый сплав ВолКар исследованы зависимости максимальной температуры, скорости роста температуры и температурных напряжений от плотности теплового потока (q = 1012 – 1016 Вт/м2) для разных времён его действия (t=10-16 – 10-10 c), также получены зависимости объема нанокластера при радиусах пятна контакта R=5·10-7, R=10-6 м от технологических параметров обработки, что позволило получить требуемые технологические параметры для получения наноструктур с применением фемтосекундного лазера.

In the case of the action of femtosecond laser VolKar hard alloy investigated over-dependence of maximum temperature, temperature rise rate and temperature stresses on the heat flux density (q = 1012 - 1016 W / m2) for different times of its operation (t = 10-16 - 10- 10 c), as prepared according nanocluster volume at the contact patch radii R = 5 · 10-7, R = 10-6 m from the technological machining parameters as possible to obtain the required process parameters for obtaining nanostructures using a femtosecond laser.
Femtosecond laser treatment from "Volkar" to create nanostructured layer on it
Keywords: фемтосекундный лазер; технологические параметры лазера; режущий инструмент; твердий сплав "ВолКар"; износостойкость; femtosecond laser; technological parameters; solid alloy "VolKar"; cutting tools; nanostructured layers